2014
DOI: 10.1111/bju.12783
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single‐site (LESS) robot‐assisted partial nephrectomy (RAPN) reduces postoperative wound pain without a rise in complication rates

Abstract: ObjectiveTo compare long-term functional outcomes and pain scale scores of patients who underwent laparoendoscopic single-site (LESS)-robot-assisted partial nephrectomy (RAPN) to those who underwent conventional RAPN (C-RAPN), as LESS surgery is increasingly being adopted by urologists worldwide to reduce morbidities and scarring associated with surgical interventions. Patients and MethodsIn all, 167 consecutive patients who had RAPN were identified from our Institutional Review Board-approved computerised dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Ten studies reported about radical nephrectomy (RN) [12–17,21,22–24]. Two studies were about partial nephrectomy (PN) [19,20]. Both RN and PN were reported by Kim et al [18], so we used Kim (RN) and Kim (PN) as RN and PN in the present study, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies reported about radical nephrectomy (RN) [12–17,21,22–24]. Two studies were about partial nephrectomy (PN) [19,20]. Both RN and PN were reported by Kim et al [18], so we used Kim (RN) and Kim (PN) as RN and PN in the present study, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Both RN and PN were reported by Kim et al [18], so we used Kim (RN) and Kim (PN) as RN and PN in the present study, respectively. Two studies reported robot-assisted nephrectomy [14,19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the preceding paper, Shin et al. report outcomes comparing conventional robot‐assisted partial nephrectomy (C‐RAPN) with laparoendoscopic single‐site (LESS)‐RAPN. This study is a follow‐up of their recently published paper on the same cohort of patients on trifecta of PN .…”
mentioning
confidence: 99%